The Concept of Halal Value Chain as a Sharia Marketing Strategy: A Literature Review - Dinda Novaberliana Putri; Dwi Novaria Misidawati (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the development of the Halal Value Chain (HVC) ecosystem in Indonesia, focusing on the challenges of halal certification and logistics, and to evaluate its strategic implications for sharia marketing and consumer purchasing decisions. This research utilizes a qualitative method with a literature review approach (library research). Data were collected from reputable scientific journals, books, and official reports published between, analyzed using content analysis to synthesize trends and structural barriers in the halal industry. The findings indicate that HVC functions as a critical ecosystem integrating upstream-to-downstream processes to ensure "Halalan Thoyyiban" integrity. While HVC positively influences consumer trust, brand image, and loyalty, its implementation in Indonesia is hindered by regulatory fragmentation, high certification costs for MSMEs, and a lack of integrated halal logistics infrastructure. Furthermore, the adoption of digital technologies like blockchain remains low. Conclusion: The study concludes that HVC is not merely a compliance mechanism but a fundamental value framework for ethical sharia marketing. Strengthening the HVC ecosystem through regulatory harmonization, infrastructure development, and digitalization is essential to enhance Indonesia's competitiveness as a global halal industry hub.